2017
DOI: 10.1177/1059601117728145
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Expertise and Social Status on Team Member Influence and the Moderating Roles of Intragroup Conflicts

Abstract: Drawing on expectation states theory and expertise utilization literature, we examine the effects of team members’ actual expertise and social status on the degree of influence they exert over team processes via perceived expertise. We also explore the conditions under which teams rely on perceived expertise versus social status in determining influence relationships in teams. To do so, we present a contingency model in which the salience of expertise and social status depends on the types of intragroup confli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 93 publications
(146 reference statements)
0
8
0
Order By: Relevance
“…In the context of organization management, EST provides a theoretical framework to conceptualize the factors that contribute to job satisfaction based on information from the surrounding environment [ 25 ]. EST indicates how performance expectations about others are constructed within the organization based on informational clues [ 26 ]. Indeed, it helps to understand the process of constructing expectations, which determines the behavior of task force members.…”
Section: Methodsmentioning
confidence: 99%
“…In the context of organization management, EST provides a theoretical framework to conceptualize the factors that contribute to job satisfaction based on information from the surrounding environment [ 25 ]. EST indicates how performance expectations about others are constructed within the organization based on informational clues [ 26 ]. Indeed, it helps to understand the process of constructing expectations, which determines the behavior of task force members.…”
Section: Methodsmentioning
confidence: 99%
“…Researchers have identified three distinct types of intragroup conflict: relationship conflict, task conflict and process conflict (Adair et al , 2017). Relationship conflict or emotional conflict indicates a presence of interpersonal incompatibility and arguments caused by tension, animosity, and annoyance among team members (Hong et al , 2017). Relationship conflict indicates disrespect and includes expressions of interpersonal tension and rejection, thus threatening interpersonal relationships and the fundamental goal of group membership (Baumeister and Leary, 1995; De Dreu and Gelfand, 2008; Meier et al , 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Relationship conflict indicates disrespect and includes expressions of interpersonal tension and rejection, thus threatening interpersonal relationships and the fundamental goal of group membership (Baumeister and Leary, 1995; De Dreu and Gelfand, 2008; Meier et al , 2013). Task or cognitive conflicts include differences in viewpoints, ideas, and opinions (Hong et al , 2017). Task conflicts are not typically linked to team members (Jehn, 1995) and do not indicate disrespect or rejection (Meier et al , 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The two most common theoretical bases are social categorization theory and information strategy theory. The former suggests that team otherness and diversity hinder team cooperation, which is adverse to the improvement of team human relations (Hong et al, 2019 ); the latter, based on the information and decision-making theory, holds that knowledge otherness and diversity play a positive role in promoting team information acquisition and new knowledge generation (Leroy et al, 2021 ). Therefore, it can be assumed according to the information process theory that the cognition and skills heterogeneity among team members will promote more comprehensive communication and task information sharing within the team, thereby improving the effectiveness of team information and knowledge processing.…”
Section: Theory and Hypothesis Developmentmentioning
confidence: 99%
“…The composition heterogeneity of entrepreneurial team is supposed to enhance the decision-making level of entrepreneurial team by improving the team's knowledge resource pool (Bell et al, 2018 ; Sherf et al, 2018 ), but some studies have shown that the role of team heterogeneity is not always positive (Tsai and Hsu, 2019 ). For some teams, the differences of ideas and values brought by background heterogeneity will increase the inter-team conflict, reduce team cohesiveness, and affect the operation efficiency of the team (Hong et al, 2019 ). This implies that the impact of team heterogeneity on entrepreneurial decision-making may be inconsistent.…”
Section: Introductionmentioning
confidence: 99%